2018
DOI: 10.1186/s13104-018-3465-8
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of three rapid screening assays for detection of antibodies to hepatitis C virus in Cameroon

Abstract: ObjectiveThis study was aimed at evaluating the performance of three CE-marked rapid diagnostic tests (RDTs): Multisure-HCV, First Response® and Toyo®; for screening anti- HCV antibody using plasma samples.ResultsOverall, 200 plasma samples were used. Sensibility and specificity of these RDTs range from 71 to 99 and 78 to 100% respectively. Multisure scored a sensitivity at 99% (95% CI 97–100%) and First Response reached a specificity at 90% (95% CI 85–94.9%). Further studies should be conducted to establish a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
2
1
0
Order By: Relevance
“…In HIV-uninfected plasma samples in this study, the performance of the 13 RDTs was high; all tests met the WHO specificity criteria and 11 of 13 met the sensitivity criteria for 1 or both lots. This is consistent with previous studies demonstrating high sensitivity and specificity of the SD Bioline [ 10 ], First Response HCV Card Test [ 14 ], and OraQuick HCV [ 9 , 10 , 15 ] in plasma samples, and high performance of a number of the RDTs in other sample types including serum and oral fluid [ 9 , 10 , 16–19 ]. In 2 systematic reviews of HCV RDTs that included studies with varying designs, references and sample types, overall pooled sensitivity was 98%–99% [ 17 , 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…In HIV-uninfected plasma samples in this study, the performance of the 13 RDTs was high; all tests met the WHO specificity criteria and 11 of 13 met the sensitivity criteria for 1 or both lots. This is consistent with previous studies demonstrating high sensitivity and specificity of the SD Bioline [ 10 ], First Response HCV Card Test [ 14 ], and OraQuick HCV [ 9 , 10 , 15 ] in plasma samples, and high performance of a number of the RDTs in other sample types including serum and oral fluid [ 9 , 10 , 16–19 ]. In 2 systematic reviews of HCV RDTs that included studies with varying designs, references and sample types, overall pooled sensitivity was 98%–99% [ 17 , 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we constructed HCV antibody basic panel, analytical specificity panel, mixed titre performance panel, characteristic panel, and commercially seroconversion panel, commercially genotype qualification panel to evaluate the performance of the HCV RDT kits. The basic panel results showed that the clinical sensitivity and clinical specificity of the seven HCV RDT kits ranged from 94% (95% CI: 83.2–98.6) to 100% (95% CI: 91.5–100), which was consistent with previous studies that the sensitivities of RDTs have varied from 90.8% to 99.9% and the specificities have varied from 92.1% to 99.9% 12,13 . The data suggest that HCV RDT kits evaluated in this study have high clinical sensitivity and clinical specificity to detect HCV infection.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, early detection ability of RDT kit was also analysed by using HCV seroconversion panels 5,12,17 . It was found that the early detection time of A, E and G reagent was earlier than that of the reference assay, which indicated that the early detection ability of HCV RDT kit was roughly the same as that of ELISA.…”
Section: Discussionmentioning
confidence: 98%